The pharmacodynamics of dexmedetomidine in elderly cardiac patients undergoing analgosedation in the ICU - Ber, Justyna Alicja; Malec, Mirosław; Bienert, Agnieszka; Nowicka, Małgorzata; Żurański, Łukasz; Grześkowiak, Edmund; Hartmann-Sobczyńska, Roma; Sobczyński, Paweł (Journal of Medical Science, 2018)
Aim. This study aimed to evaluate the pharmacodynamics of dexmedetomidine in elderly cardiac patients.Material and Methods. Twelve patients of 60 years or older and need for analgesia after surgery or as a result of critical health conditions were included into our study. Dexmedetomidine was administered intravenously as a continuous infusion without the initial dose. At the beginning the infusion was started at the rate of 0.7 µg/kg/h and then it was continued in the range of 0.17–1.39 µg/kg/h according to desired level of sedation. Information about heart rate, systolic, diastolic and mean arterial blood pressure, bispectral index and cardiac index were collected a few minutes before, during and in 12 hours after infusion of dexmedetomidine.Results. The hemodynamic data as well as BIS level were collected from 12 patients. The duration of dexmedetomidine infusion was less than 9 hours. For each patient the reduction in blood pressure and heart rate compared to the value before dexmedetomidine infusion was observed. We did not observe bradycardia in any patient. Appropriate sedation level was achieved using only dexmedetomidine and ranged from 60 to 80. In only 2 cases it was necessary to give a single dose of another sedative.Conclusions. To conclude, in the patients’ population involved in the study, which included older cardiac patients dexmedetomidne has been shown as a sedative agent which enabled to achieve desire level of sedation in the recommended ranges without episodes of bradycardia, however hypotension events were noted.
Keywords: dexmedetomidine; pharmacodynamics; bradycardia; hypotension; sedation